Palatogingival grooves associated with periodontal bone Loss of maxillary incisors in a Chinese population. (6th October 2021) - Zhang, Rui; Xiong, Jie; Haapasalo, Markus; Shen, Ya; Meng, Liuyan
Abstract: This study aimed to investigate the prevalence of palatogingival grooves (PGGs) in a Chinese population and the relationship between different types of PGGs and periodontal bone loss. CBCT images of 1715 patients were included in the study. The prevalence of PGGs of the maxillary incisors by sex and tooth type was analysed. The severity of alveolar bone loss in different types of PGGs was assessed. The reasons for taking the CBCT from patients with PGGs were collected. The frequency of PGGs in males (10.16%) was higher than that in females (7.05%) ( P < 0.05). PGGs were present more often in maxillary lateral incisors (4.5%) than in maxillary central incisors (0.29%). Compared with other types of PGGs, the type I PGGs were the most prevalent configuration and accompanied with less severity of alveolar bone loss ( P < 0.05). Less than half of PGGs cases (47.9%) were prescribed CBCT examination because of the PGGs observed or suspected clinically. The prevalence of PGGs in a Chinese population was higher in males than in females. The different types of PGGs might lead to different severity of periodontal bone destruction. Clinicians should be aware of the presence of PGGs in maxillary incisors, particularly maxillary lateral incisors.